The influence of corporate governance on succession planning and organizational performance in Chinese family firms - Li, Zeyu; Mustapha, Mazlina; Sheikh Hassan, Ahmad Fahmi; Saidin, Saidatunur Fauzi (Emerald Publishing, 2024)
Purpose: This study examines the impact of corporate governance on succession planning and organizational performance. Drawing on agency theory, the main purpose of this study is to identify the effect of corporate governance on succession planning by measuring the different characteristics of the board of directors. Design/methodology/approach: This multi-quantitative research used primary and archival data. A total of 281 valid questionnaires were collected from Chinese listed family firms to gauge succession planning. Relevant archival data were obtained to measure board characteristics and organizational performance. All hypotheses were examined through structural equation modeling. Findings: The outcomes indicate that corporate governance positively influences succession planning and, in turn, boosts superior organizational performance, which uncovers the mediating effect of succession planning on the relationship between corporate governance and organizational performance. Our findings reveal that board independence and education facilitate the development of succession planning, which is crucial in the family business’s life cycle. Originality/value: The results of this study contribute to management succession, strategic management and leadership research by demonstrating how corporate governance fosters organizational performance through succession planning, thereby expanding the application scenarios of agency theory in family firms. Additionally, the article also enriches our understanding of how family businesses apply sound governance structures to promote organizational strategic decision-making during the succession process.